Environmental Greening in Residential Vacant Land: A Community Service Initiative at Griya Muncang Asri Housing, Tasikmalaya City - Muhammad Al Mighwar (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
This abstract summarizes a community service initiative focused on environmental greening in residential vacant land within the Griya Muncang Asri Housing area in Tasikmalaya City. The project aims to address the issue of unused land by promoting sustainable practices and enhancing the local environment. The initiative includes engaging residents in collaborative efforts to transform vacant lots into green spaces that contribute to ecological conservation, aesthetic improvement, and community well-being. By implementing innovative strategies such as urban gardening, tree planting, and sustainable landscaping, the project aims to create a greener and more vibrant living environment. The initiative also emphasizes community participation and education, empowering residents with knowledge and skills related to environmental conservation and sustainable land management. Through this community service initiative, the project seeks to foster a sense of ownership, pride, and social cohesion among residents while promoting sustainable development practices in residential areas.